Report of the expert consultation on implementation iáues aáociated with listing commercially exploited aquatic species on cites appendices. Rome (Italy). 25-28 May 2004 - FAO, Rome (Italy) (Rome (Italy), 2004)
Sumario (En)
no. 741
Keywords: ANIMALES ACUATICOS; ACUICULTURA; PESCA; DESARROLLO PESQUERO; COMERCIO; ORDENACION DE RECURSOS; MERCADEO